Pengembangan Media Pembelajaran Nahwu Berbasis Game untuk Meningkatkan Pemahaman Kitab Matan Al-Jurumiyyah di Madrasah Tarbiyah Islamiyah Canduang - Darmawati, Gusnita; Wahyuni, Widya; Hanafi, Imam (Intellect : Indonesian Journal of Learning and Technological Innovation, 2024)
This research aims to develop a valid, practical, and effective game-based nahwu learning medium for the first grade students of Madrasah Tarbiyah Islamiyah (MTI) Canduang. The background of this research is the low interest and learning outcomes of students in understanding nahwu material, particularly in studying the book of Matan Al-Jurumiyyah which is loaded with abstract grammatical terms. The method used is Research and Development (R&D) with the 4-D model approach of Thiagarajan, Semmel, and Semmel which includes the define, design, develop, and disseminate stages. The product is developed in the form of interactive media in the form of educational games based on android with nahwu material content, audio narration, animative visualization, and evaluative quizzes. The results of this study will be proven using product tests that include product validity tests tested on experts, practicality tests tested on teachers, and effectiveness tests tested on students. To see the results of each product test, the authors used questionnaires in the data collection. From this study, a validity feasibility result with an average of 0.92 was classified as very valid, while a feasibility result with an average of 93 that belonged to the very practical category and a feasibility result of effectiveness was obtained with an average of 0.85 with a very high category. The contributions of this research include: (1) strengthening the theory of game-based learning in the context of Islamic education; (2) providing practical solutions for madrasa teachers to teach nahwu in an engaging manner; and (3) presenting an integrative innovation between classical textual traditions and digital technology. Thus, this media serves as a model for digital transformation in Arabic language learning in madrasas. Abstrak Penelitian ini bertujuan untuk mengembangkan media pembelajaran nahwu berbasis game yang valid, praktis, dan efektif bagi siswa kelas I Madrasah Tarbiyah Islamiyah (MTI) Canduang. Latar belakang penelitian ini adalah rendahnya minat dan hasil belajar siswa dalam memahami materi nahwu, khususnya dalam mempelajari kitab Matan Al-Jurumiyyah yang sarat dengan istilah tata bahasa yang bersifat abstrak. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan 4-D dari Thiagarajan, Semmel, dan Semmel, yang meliputi tahapan define, design, develop, dan disseminate. Produk dikembangkan dalam bentuk media interaktif berupa permainan edukatif berbasis Android yang memuat konten materi nahwu, narasi audio, visualisasi animatif, serta kuis evaluatif. Hasil penelitian ini dibuktikan melalui uji validitas produk oleh para ahli, uji kepraktisan oleh guru, dan uji efektivitas oleh siswa. Data dikumpulkan menggunakan angket dan dianalisis secara kuantitatif. Hasil uji validitas menunjukkan nilai rata-rata 0,92 (kategori sangat valid), hasil uji kepraktisan memperoleh nilai rata-rata 93 (kategori sangat praktis), dan hasil uji efektivitas mencapai rata-rata 0,85 (kategori sangat tinggi). Kontribusi penelitian ini meliputi: (1) memperkuat teori game-based learning dalam konteks pendidikan Islam; (2) menyediakan solusi praktis bagi guru madrasah untuk mengajarkan nahwu secara menarik; dan (3) menghadirkan inovasi integratif antara tradisi kitab klasik dan teknologi digital. Dengan demikian, media ini berperan sebagai model transformasi digital dalam pembelajaran bahasa Arab di madrasah.